Effects of Water Stress on Plant Canopy, Yield Attributes and Yield of Potato - Mahmud, Abdullah-Al; Hossain, M. Mofazzal; Zakaria, Mohammad; Mian, M.A. Khaleque; Karim, M. Abdul (Agriculture and Natural Resources, 2015)
Four potato clones of the International Potato Center with one check variety (Asterix) were planted in the third week of November 2010 at the Horticultural Research Farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University to observe the effect of water stress on plant canopy growth, development and yield of potato. Plant heights, the number of leaves and leaf area of all the clones were significantly affected by water stress. Tolerant clones produced greater tuber dry matter under stressed conditions. The largest reduction in yield (greater than 50%) was found in the susceptible clones; the tolerant clones showed comparatively less yield reduction (less than 50%). The yield reduction caused by water stress was attributed mainly to the reduction in number of tubers per plant with small-sized tuber production. In addition, the percentage difference in dry matter in the tubers of susceptible clones was greater than in the tolerant clones due to the utilization of water from the tubers in the water stress treatment.